The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00454-019-00122-w
|View full text |Cite
|
Sign up to set email alerts
|

Bisectors and Pinned Distances

Abstract: We prove, under suitable conditions, a lower bound on the number of pinned distances determined by small subsets of two-dimensional vector spaces over fields. For finite subsets of the Euclidean plane we prove an upper bound for their bisector energy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…They proved that for E ⊂ F 2 p with p ≡ 3 mod 4, if |E| ≪ p . This result has been recently improved by Lund and Petridis in [9], namely, they indicated that |∆(E)| |E| 1 2 + 3 74 , under the condition that |E| ≪ p 8/5 with p ≡ 3 mod 4.…”
Section: Introductionmentioning
confidence: 80%
“…They proved that for E ⊂ F 2 p with p ≡ 3 mod 4, if |E| ≪ p . This result has been recently improved by Lund and Petridis in [9], namely, they indicated that |∆(E)| |E| 1 2 + 3 74 , under the condition that |E| ≪ p 8/5 with p ≡ 3 mod 4.…”
Section: Introductionmentioning
confidence: 80%
“…We apply Theorem 7 to 𝑃 and Π, claiming that the number of collinear points is bounded by 𝑀. This claim is a direct consequence of [22,Lemma 2.2]. Firstly, note that points in 𝑃 ∶= 𝜅(𝐺 ′ 𝑟 ) correspond to a segment 𝑠 𝑟 ∈ 𝑆 𝑟 in the configuration space; 𝑠 𝑟 determines the rigid motion g via the relation g −1 (𝜏(𝑠 𝑟 )) = (𝑎, 𝑎 ′ ) and 𝜅(g) is a point in 𝑃.…”
Section: Proof Of Theorem 11mentioning
confidence: 90%
“…If 𝑏 ≠ 𝑏 ′ , then it's easy to conclude that 𝑑(𝑎, 𝑏) = 𝑑(𝑎, 𝑏 ′ ) = 0 (see, e.g. [22,Lemma 2.3]). This is a contradiction, so there are |𝐴| 2 such triples.…”
Section: Isosceles Triangles and Bisector Energymentioning
confidence: 99%
“…The best current lower bound is |E| 2/3 due to Murphy, Petridis, Pham, Rudnev and Stevens [19]. We also note that it seems very difficult to extend the methods in [12,16,11,19] to the Minkowski and parabola distance functions. We now take advantage of the generality of Theorem 1.1 to study algebraic distances between two sets in F 3 p , where one set lies on a plane and the other set is arbitrary.…”
Section: Pinned Algebraic Distancesmentioning
confidence: 95%
“…When f (x, y) = x 2 + y 2 , Theorem 6.1 was first proved by Stevens and de Zeeuw in [24] by using a point-line incidence bound. The exponent 8 15 was improved to 1 2 + 149 4214 by Iosevich, Koh, Pham, Shen and Vinh [12], then to 1 2 + 3 74 by Lund and Petridis [16] and to 1 2 + 69 1558 by Iosevich, Koh and Pham [11]. The best current lower bound is |E| 2/3 due to Murphy, Petridis, Pham, Rudnev and Stevens [19].…”
Section: Pinned Algebraic Distancesmentioning
confidence: 98%